FR2.2: Gender assessement of Potato Traits: A G+ Product Profiling application - Mwende, J.; Mayanja, S.; Nyaga, J.; Sinelle, S.; Renou, C.; Onyango, C.; Hareau, G.; Polar, Vivian; Ashby, Jacqueline A.; Okello, J.J. (International Potato Center, 2022)
In Sub-Saharan Africa, low adoption of improved varieties has been linked to breeding programs failing to consider end-user trait preferences and the interplay with gender. Recently, efforts have commenced assessing the gender responsiveness of product profile proposals during variety development, testing, and dissemination. The study uses a multi-stage approach to examine the gender responsiveness of Kenya's target table potato product profile. First, the G+ product profile tool was employed to examine the likelihood of the selected traits exacerbating gender disparity along four domains: unpaid labour, access to farm and external resources and control over benefits based on a literature review. Then key informant interviews and a multi-stakeholder workshop followed to build consensus on the gendered assessment. Findings show that tuber yield is associated with increased demand for women's unpaid labour during harvesting and sorting and greater requirement for inputs to which women have limited access. Respondents in the multi-stakeholder workshop highlighted the potential of dry matter to increase women's unpaid labour due to increased preparation time. Moreover, the trait may increase marketability, thus attracting men and displacing female processors from income-generating nodes. We thus recommend that gender-responsive techniques designed by a multidisciplinary team and complementary technologies should accompany the dissemination and promotion of the resultant variety. This would minimise gender inequalities and spur equal benefits for men and women.